EFFECT OF A TRAINING PROGRAM IN RESISTIVE AND AEROBIC TRAINING PROGRAM AND TEENS WITH OVERWEIGHT AND OBESITY (Fiep Bulletin - online, 2015)
Aimed to assess the effect of concurrent training on body composition and blood markers in adolescent overweight. Experimental study with adolescents of both sexes, aged between 12 and 16 years pubescent, randomized into two groups: (GI) concurrent training 2:04 months (n = 7) and (GC) and non-participant training (n = 10 ) to the Center of Obesity in Natal, RN. We evaluated weight, height, BMI, WC, DCTR, DCSB, ?DC and% G and lipid profile, glucose, triglycerides, LDL-C, HDL-C, Total cholesterol. We used the General Linear Models (GLM) for repeated measures, between the nonparametric and parametric t test groups U test and Spearman (?) p = 0.05. In outcome between the intervention groups after 02 months and found significant differences for DCSB, ?DC and G%, triglyceride and total cholesterol, and control groups after 02 months Weight, DCTR, DCSB, ?DC and G%, Triglycerides, LDL-C, HDL-C and Total Cholesterol in the intervention groups and after 4 months for weight, BMI, WC, DCSB, ?DC and G%, Triglycerides, LDL-C, HDL-C, Total Cholesterol. In the control group after 04 months and did not find significant differences for height and glucose. Thus we conclude that the method of concurrent training was effective in reducing body weight, central adiposity, body fat and lipid profile after 16 weeks of intervention. Blood glucose despite having presented significant changes among the three evaluations observed a trend toward greater reduction in the first two months.
Keywords: Physical Activity; school; obesity; training.